2008
DOI: 10.1128/aem.01237-08
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Variability of Single-Cell Lag Times for Listeria innocua Populations after Sublethal and Lethal Heat Treatments

Abstract: Optical density measurements were used to estimate the effect of heat treatments on the single-cell lag times of Listeria innocua fitted to a shifted gamma distribution. The single-cell lag time was subdivided into repair time (the shift of the distribution assumed to be uniform for all cells) and adjustment time (varying randomly from cell to cell). After heat treatments in which all of the cells recovered (sublethal), the repair time and the mean and the variance of the single-cell adjustment time increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…In addition, other studies of the effects of heat treatments and other stresses on the variability of cell responses have focused on the lag time. Regarding the coefficient of variation of the lag time, some authors have reported that it is not affected by the intensity of the heat treatment (14) while others have found a general increase after heat treatments and other stresses (6,11). Therefore, the heterogeneity of the surviving population may also be reflected by greater variability in the repair time needed for the survivors to start dividing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, other studies of the effects of heat treatments and other stresses on the variability of cell responses have focused on the lag time. Regarding the coefficient of variation of the lag time, some authors have reported that it is not affected by the intensity of the heat treatment (14) while others have found a general increase after heat treatments and other stresses (6,11). Therefore, the heterogeneity of the surviving population may also be reflected by greater variability in the repair time needed for the survivors to start dividing.…”
Section: Discussionmentioning
confidence: 99%
“…Stochastic models for the growth of populations have been developed based on the experimentally measured distributions for the lag times of single cells and spores (13,14,18,19,26). In those models, the distribution of the initial number of cells was assumed to be independent of the heat treatment or previous stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1e100 CFU g À1 to measure the potential for growth and the impact of microbial competition, but numbers need to be sufficient so that they are above the detection level throughout the length of the study. Low inocula of several different L. monocytogenes strains should be used in challenge studies to account for variability in results, e.g., the duration of the lag phase (Beaufort et al, 2008;Métris, George, Mackey, & Baranyi, 2008). To allay concerns over exceeding a regulatory limit of 100 CFU g À1 , the challenge testing should never be carried out with levels above 50e100 CFU g À1 .…”
Section: Challenge Studiesmentioning
confidence: 99%
“…For several years, it has been accepted that the accurate prediction of the behavior of food-borne pathogens contaminating food with a few cells requires a single-cell approach, taking into account the variability of individual cell lag times, since this variability will strongly influence the lag phase duration of the bacterial population (9)(10)(11)(12)(13). More recently, studies also emphasized the need to take into account the single-cell growth probability when assessing the behavior of these food-borne bacteria (14)(15)(16)(17).…”
mentioning
confidence: 99%